2010
DOI: 10.1128/iai.00522-10
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Pathogenic Bacteria and Intrauterine Leukocytes Triggers Alternative Molecular Signaling Cascades Leading to Labor in Women

Abstract: Increased risk of preterm labor has been linked to cervicovaginal infection with Ureaplasma urealyticum and group B streptococci. Although various experimental models have been developed to study the role of amniochorion infection in preterm labor, they typically exclude the initial interaction between intrauterine leukocytes (recruited from decidual vessels into the avascular fetal membranes) and infecting bacteria. In this work, we ascertained whether inflammatory molecules secreted by bacterium-activated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Examples include harmful triggering of cellular signaling cascades, [1] invasion of host cells, [2] or biofilm formation. [3] One of the most common infectious diseases caused by bacterial adhesion are urinary tract A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 2 infections (UTI).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include harmful triggering of cellular signaling cascades, [1] invasion of host cells, [2] or biofilm formation. [3] One of the most common infectious diseases caused by bacterial adhesion are urinary tract A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 2 infections (UTI).…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines stimulate the secretion of other mediators, including prostaglandin E 2 and matrix metalloproteinases, which participate in the weakening of the fetal membranes and consequent disruption (Estrada-Gutierrez et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of phospholipases A and C has been suggested to be the means by which ureaplasmas may initiate preterm labor by liberating arachidonic acid and altering prostaglandin synthesis (De Silva & Quinn, 1986). In addition, recently we reported that the interaction between U. urealyticum, intrauterine leukocytes and fetal membranes results in the secretion of high amounts of IL-1b and prostaglandin E2, which could induce uterine contraction leading to preterm labor (Estrada et al, 2010). Isolation of U. urealyticum from chorioamnion has been consistently associated with histological chorioamnionitis and is inversely related to birth weight, even when adjusting for duration of labor, rupture of the fetal membranes, and the presence of other bacteria [Cassel et al, 1993;.…”
Section: Ureaplasma Urealyticum and Ureaplasma Parvum In Urogenital Amentioning
confidence: 99%